How to contain a tapeworm epidemic—testing the efficiency of different catch methods to reduce the translocated final host Esox lucius in an alpine lake. Issue 5 (10th November 2015) - Schaufler, Gishild; Stögner, Claudia; Gassner, Hubert; Kaiser, Roland; Schabetsberger, Robert
Abstract : Half a century after introducing the final host Northern pike ( Esox lucius L. 1758) into Lake Grundlsee in Austria, a sudden massive infection with the pike tapeworm Triaenophorus crassus Forel 1868 was noticed in the population of the intermediate host Arctic charr ( Salvelinus umbla (L. 1758)) and led to the closure of this famous fishery. In an effort to contain the epidemic, a total of 1163 pike were removed over a period of three years (2008–2010). The efficiencies of gill and fyke netting as well as electro and spear fishing were assessed. All four methods were costly with EUR 37–371 to catch a single fish. During intensive fishing, catch per unit effort and fish lengths of pike declined. Fyke netting coupled with electro fishing turned out to be the most practicable strategy to reduce the pike stock. After another three years, prevalence of T. crassus in Arctic charr could be reduced by 40% in 2013. However, it will be impossible to completely eradicate pike and its parasite in the lake.